Effect of silver nanoparticles on system performance and microbial community dynamics in a sequencing batch reactor. (1st September 2016) - Qiu, Guanglei; Wirianto, Kawi; Sun, Yuanlong; Ting, Yen-Peng
Abstract: The effect of silver nanoparticles on the system performance and the bacterial community dynamics in a sequencing batch reactor was investigated, along with the removal and the fate of silver nanoparticles within the system. Results showed that silver nanoparticles did not significantly affect organic matters removal, nitrification and denitrification. However, adverse effects were observed on sludge settleabilities, which were related to the over-production of extracellular polymeric substances and a sequential change in activated sludge structure and morphology. Polymerase chain reaction–Denaturing gradient gel electrophoresis revealed that silver nanoparticles caused significant shifts in bacterial community structures. Different species were affected and eliminated at each dosage of silver nanoparticles. Silver nanoparticles were effectively removed in the bioreactor, with the main removal pathway being deposited in the activated sludge. Highlights: Silver nanoparticles did not significantly affect nitrogen and organic matter removal. Silver nanoparticles resulted in over-production of extracellular polymeric substances. Silver nanoparticles caused poorer sludge settleability. Different bacterial species were affected at different silver nanoparticles concentrations. Silver nanoparticles were effectively removed via deposit in the activated sludge.